The Educational Thought of Ibn Sina and Ibn Khaldun, "A Historical View" (Journal of the College of Basic Education, 2022)
He enriched the Arab-Islamic educational thought, which is rich and abundant with science and knowledge, because the study of educational thought makes the reader draw lessons and lessons to illuminate the paths before him, as solving present problems in the light of understanding the past, because education is the product of a long historical labor and a deep-rooted human experience, and it constantly bears the shape of the vessel that was born It has all its properties since antiquity. It is a mistake to believe that heritage is something that has passed and has become a thing for history and museums, rather it is a manifestation of the genius of the Arab and Islamic nation.Therefore, it is possible to study educational thought in our Arab and Islamic heritage. Despite the care of heritage, our writings, our studies, and our knowledge of philosophy and educational thought are still few in a narrow space about our history, its media, and our philosophers such as Ibn Sina and Ibn Khaldun, who appreciated the importance of education, curriculum, teaching methods, student The teacher is in the life of the individual and the nation and prepares him for the integration of the human being in terms of the physical mental, emotional and moral aspects. The school is a social institution and an effective means through which cultural changes and common national goals can be achieved. He placed their educational and educational philosophy within a national framework with a purposeful and directed educational thought. He emphasized that science is of great value if a person believes in it to the extent that he desires that knowledge is not information as much as it is It is a method and method for obtaining this information, and it is the main factor in the success of the educational process, and it is one of the most important elements of education. Therefore, it needs more research and study in the origins of our thought to form our Arab and Islamic nation. The research aims at rooting and strengthening our cultural and educational thought and knowing what the two philosophers (Avicenna and Ibn Khaldun) added to our educational system, in order to enhance knowledge of our national heritage and its role in human civilization when studied by our students, and to enrich the contemporary educational library with authentic and deep-rooted educational studies within educational disciplines